Büyük veri üzerine perspektif bir bakiş - Demirol, Doygun; Das, Resul; Hanbay, Davut (Institute of Electrical and Electronics Engineers Inc., 2019)
Data, which is the new trend of 21st century, has made difficult to extract meaningful information from itself because of its increasing volume and variety Big data platforms and tools to analyze the size and type of data that cannot be processed by traditional methods have brought new perspectives to data analytics. Big Data are gathered from non-Traditional sources such as wireless sensors, blogs, social media, emails etc. In addition, companies can make better insights of large data sets by using large data analysis mechanisms. In this study, the definition of big data, its relationship with other technologies, technologies used in big data area and general information about analysis techniques are given. © 2019 IEEE.
2019 International Conference on Artificial Intelligence and Data Processing Symposium, IDAP 2019 -- 21 September 2019 through 22 September 2019 -- Malatya -- 153040
Keywords: Big Data; Big Data Analysis; Data Mining; Machine Learning